The Influence Of Non-Cash Payment Systems On Financial Behavior With Digital Culture As A Moderating Variable - Kusiyah; Tita Safitriawati; Dian Indah Sari; Andalia; Endi Rustendi (Yayasan Inovasi Kemajuan Intelektual, 2022)
This study aims to analyze the influence of cashless payment systems on individual financial behavior, with digital culture as a moderating variable. In an era of rapid technological transformation, the shift from cash-based transactions to digital platforms has changed the way consumers perceive and manage the value of money. Using a quantitative approach, this study evaluates how ease of access and digital payment features trigger different consumption behaviors. The results show that cashless payment systems have a positive and significant influence on financial behavior that tends to be consumptive, but can improve financial record-keeping efficiency if managed properly. Furthermore, digital culture was found to strengthen this influence: individuals with high levels of digital literacy and adaptation were more likely to adopt this payment technology, but were also more prone to impulsive spending. These findings provide important implications for regulators and financial service providers to improve digital financial literacy education to mitigate the risk of negative financial behavior in society.